A Comparative Analysis of The Trial of Dedan Kimathi, The Trials of Oba Ovonramwen and My Children! My Africa!: Implications for Postmodernist African Society - Owonibi, Sola; Akinbulejo, Sunday (Àgídìgbo: ABUAD Journal of the Humanities, 2016)
Between modernism and postmodernism, critics have continued to appraise literary texts in the light of their contributions to and implications for the society. Opinions have continued to vary on the most suitable theory for coming to terms with prevalent conditions in contemporary society. Modernism precedes postmodernism and there is the rationalisation that it is thus more suitable for the contemporary African society. However, opposition to this view cannot be waved aside in view of evident effects of postmodernist ideal on the society. Hence, this paper attempts to further investigate the relevance of postmodernism to the African society in its struggle against socio-political aberrations. The three texts selected for this study have the potential of revealing a historical trend of struggle through early colonialism in West Africa to armed struggle in East Africa and late anti-apartheid struggle in South Africa. The study reveals that, historically, attempts by Africans to carry on spirited united struggle have usually been undermined by disunity and sabotage. This has again authenticated the skepticism about the tenets of postmodernism being able to effectively aid successful struggle against social-political aberrations on the African continent. Perhaps a blend of modernism and postmodernism would serve better.